Basic Behavioral Processes Involved in Procrastination - Zentall, Thomas R. (Frontiers in Psychology, 2021)
Procrastination involves putting off engaging in a course of action. An important approach to procrastination is its relation to several behavioral procedures that have been studied humans and other animals. For example, in delay discounting, smaller rewards that come sooner are often preferred over larger rewards that come later. In the context of delay discounting, procrastination can be viewed as the preference for an immediate competing activity over the delay to work on the required task. Another analog to procrastination can be seen in free operant, temporal avoidance (or Sidman avoidance) in which an animal will receive a shock if an interval passes without a specified response. Once animals learn about the interval, they often procrastinate. That is, they often wait until the interval has almost passed before responding. Finally, research with animals suggests that the persistence of procrastination may involve a form of negative reinforcement associated with the sudden decline in anxiety (or any aversive event) when the task is completed prior to the deadline. Research with animals suggests that the mechanisms responsible for human procrastination may involve systems that derive from several procedures known to produce similar behavior animals.